Concepción y dinámica familiar: Análisis desde la percepción de un grupo de niños de cuatro años (2019)
In order to analyze the perception of a group of 4-year-old children about family conception and dynamics in Colombia, a qualitative approach research with phenomenological design is carried out. It works with 35 children belonging to socioeconomic strata 1 and 2 catalogued as low resources by the System for the Selection of Beneficiaries for Social Programs (SIS-BEN). The collection of information is done through the semi-structured interview; likewise, 14 illustrative animated representations are designed, as a visual stimulus technique, with different possible members of a family group. The results show that the concept of family for children is based on their own appraisals related to the style of attachment and upbringing they possess. On the other hand, it is evident that family dynamics is a determining factor for these children to express positive or negative perceptions of their home and family members.